Trends in Urban Newspaper Use of Farm News: A Qualitative Study - Robert G. Hays (Journal of Applied Communications, 1993)
Because large-circulation newspapers in the United States continue to serve increasingly urban audiences, there is a logical question as to what place agriculture-related news has in their pages.